Improved determination of the D → K−π+π+π− coherence factor and associated hadronic parameters from a combination of e+e-→ψ(3770)→cc̄ and pp→cc̄X data - Evans, T; Harnew, S; Libby, J; Malde, S; Rademacker, J; Wilkinson, G (Elsevier, 2016)
Measurements of the coherence factor RK3π, the average strong-phase difference δDK3π and mean amplitude ratio rDK3π for the decay D→K-π+π+π- are presented. These parameters are important inputs to the determination of the unitarity triangle angle γ in B-→DK- decays, where D designates a superposition of D0 and D-0 mesons decaying to a common final state. The results are based on a combined fit to observables obtained from a re-analysis of the CLEO-c ψ(3770) data set and those measured in a D0D-0 mixing study performed by the LHCb Collaboration.